1974
DOI: 10.3181/00379727-147-38376
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hyperthyroidism and Maturation of the Rat Hypothalamo-Hypophyseal-Adrenal Axis

Abstract: The neonatal rat exhibits a refractory period of the hypothalamo-hypophyseal-adrenal axis in response to stress which encompasses days 3-1 2 of life, an interval called the stress nonresponsive period (SNR) (1). Then, at 15 days of age, the rat responds equally to ether stress and exogenous ACTH by an increased synthesis and release of corticosterone (2). However, hypothyroidism induced by thiouracil feeding during pregnancy and lactation prevented the hypothalamo-hypophyseal-adrenal axis response to ether str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…We have demonstrated that hyperthyroidism, induced by daily T 4 injection, accelerates the maturation of the HPA axis in the rat during the early postnatal period. After T 4 treatment, our results demonstrate, as previously reported ( 3–5), significant increases in plasma corticosterone concentrations in 8‐ and 15‐day‐old rats. This increase does not seem to be secondary to a direct effect of T 4 at the adrenal gland since, in vivo and in vitro , T 4 decreases corticosterone secretion ( 21).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have demonstrated that hyperthyroidism, induced by daily T 4 injection, accelerates the maturation of the HPA axis in the rat during the early postnatal period. After T 4 treatment, our results demonstrate, as previously reported ( 3–5), significant increases in plasma corticosterone concentrations in 8‐ and 15‐day‐old rats. This increase does not seem to be secondary to a direct effect of T 4 at the adrenal gland since, in vivo and in vitro , T 4 decreases corticosterone secretion ( 21).…”
Section: Discussionsupporting
confidence: 90%
“…This period of development is named the ‘stress hyporesponsive period’, and concentrations of thyroid hormones may participate in this phenomenon. Plasma thyroxine is low at birth, rising to a peak around days 8–12 ( 2), and administration of T 4 enhances basal circulating concentrations of corticosterone during early postnatal life ( 3–5), possibly secondary to a T 4 ‐induced rise in circulating concentrations of corticosteroid binding globulin (CBG) ( 6, 7). In addition, thyroid hormones could modulate the main hypothalamic factors that stimulate ACTH release: corticotropin‐releasing factor (CRF) and arginine vasopressin (AVP) since thyroid hormones exert major influences on rat brain development, differentiation and gene expression ( 8).…”
mentioning
confidence: 99%
“…Thus, neonatal Tj administration re sults in an early increase in basal corticosterone titers and CBG levels [6,10,22] as well as in the early maturation of the adrenocortical response to stress [29]. In contrast, PTU administration during this period delays the maturation of the adrenocortical stress response and suppresses CRF-like activity in the hypothalamus [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the developmental increase in this parameter was advanced approximately 3 days in hyperthyroid animals and was delayed approximately 3 days in hypothyroid animals. Previous studies on the effects of T4 status on the in vivo response of serum corticosterone to ACTH yielded conflicting results (22)(23)(24) and their interpretation was complicated by the use of a fluorometric assay which is known to be inappropriate in young rodents (1,…”
Section: Age (Days)mentioning
confidence: 99%